Microalgae lipid and biomass for biofuel production: A comprehensive review on lipid enhancement strategies and their effects on fatty acid composition. (December 2018) - Sajjadi, Baharak; Chen, Wei-Yin; Raman, Abdul. Aziz. Abdul; Ibrahim, Shaliza
Abstract: Renewable energy sources e.g. biofuels, are the focus of this century. Economically and environmental friendly production of such energies are the challenges that limit their usages. Microalgae is one of the most promising renewable feedstocks. However, economical production of microalgae lipid in large scales is conditioned by increasing the lipid content of potential strains without losing their growth rate or by enhancing both simultaneously. Major effort and advances in this area can be made through the environmental stresses. However, such stresses not only affect the lipid content and species growth (biomass productivity) but also lipid composition. This study provides a comprehensive review on lipid enhancement strategies through environmental stresses and the synergistic or antagonistic effects of those parameters on biomass productivity and the lipid composition. This study contains two main parts. In the first part, the cellular structure, taxonomic groups, lipid accumulation and lipid compositions of the most potential species for lipid production are investigated. In the second part, the effects of nitrogen deprivation, phosphorus deprivation, salinity stress, carbon source, metal ions, pH, temperature as the most important and applicable environmental parameters on lipid content, biomass productivity/growth rate and lipid composition are investigated. Highlights: Cellular structure and taxonomy of potential microalgae for biofuel production were considered. The quality of lipid accumulation and lipid compositions of those strains were investigated. The effect of environmental stressors on lipid enhancement in those strains was investigated. The effect of stressors on biomass productivity and lipid composition was investigated.